2018
DOI: 10.12659/pjr.902524
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging in the Oral and Maxillofacial Region: Usefulness of Apparent Diffusion Coefficient Maps and Maximum Intensity Projection for Characterization of Normal Structures and Lesions

Abstract: SummaryBackgroundThe aim of this study was to investigate diffusion-weighted imaging (DWI) in the oral and maxillofacial region, with a special focus on the usefulness of apparent diffusion coefficient (ADC) maps and maximum intensity projection (MIP) for characterization of normal structures and lesions.Material/MethodsThirty-five patients who underwent magnetic resonance imaging (MRI) for diagnosis of oral and maxillofacial lesions were included in this prospective study. DWI was performed on a 1.5 T unit, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Bonello et al20 showed that DWI could provide information on microstructural tumor characteristics. Previous studies have reported that DWI and ADC maps were useful for the differential diagnosis of oral and maxillofacial lesions 1516. In our study, all cases (ORN and MRONJ) showed high signal intensity on DWI, and low signal intensity on ADC maps.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Bonello et al20 showed that DWI could provide information on microstructural tumor characteristics. Previous studies have reported that DWI and ADC maps were useful for the differential diagnosis of oral and maxillofacial lesions 1516. In our study, all cases (ORN and MRONJ) showed high signal intensity on DWI, and low signal intensity on ADC maps.…”
Section: Discussionsupporting
confidence: 63%
“…The images were acquired using a 16-MDCT apparatus (Aquilion TSX-101A; Canon Medical Systems, Otawara, Japan), a 1.5-T MR imaging system (EXCELART Vantage MRT-2003; Canon Medical Systems, Otawara, Japan), and a SNC-5100R scintigraphy apparatus (Shimadzu, Kyoto, Japan) with Tc-99m HMDP (Clear Bone Injection; Nihon Medi-Physics, Tokyo, Japan), following our institutional protocol 8141516…”
Section: Methodsmentioning
confidence: 99%
“…We used regions of interest (ROI) to calculate the ADC values on ADC maps. We placed five ROIs with similar sizes within the lesions to obtain a mean ADC value (Figure 1), following our institutional protocol 7‐9 , and ADC value were automatically measured.…”
Section: Methodsmentioning
confidence: 99%
“…DWI with apparent diffusion coefficient (ADC) maps, which provides a quantitative index of water diffusivity for each voxel that allows the visualization of the microscopic motion of water molecules within tissues, can facilitate data acquisition and processing steps without the use of ionizing radiation or contrast agents 6 . Therefore, DWI has been considered a useful imaging on diagnostic ability of ADC maps in oral and maxillofacial lesions 7‐9 . Furthermore, some studies have reported the application of DWI with the calculation of ADC in the differential diagnosis of lesions in the major salivary glands 10 and floor of the mouth 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Differentiate oral cavity abscesses from cystic/necrotic tumours. An abscess shows high signal on DWI trace images and low values on ADC maps (0.7-0.85 × 10 −3 mm 2 /s) (Figure 4), whereas a cystic/necrotic tumour usually has high values on ADC maps (>2.0 × 10 −3 mm 2 /s) [30][31][32];…”
mentioning
confidence: 99%